Stigma, Discrimination, and Public Perception: A Relationship between Screening for Mental Emotional Disorders and Public Perception of Mental Disorders - Ichdinavia Harsaya; Alifiati Fitrikasari; Innawati Yusuf; Elly Noerhidajati; Yetty Movieta Nency (Universitas Negeri Semarang, 2021)
Mental-emotional disorder is a condition of emotional changes that can develop into a pathological state, with a prevalence of 9.8% in people over 15 years of age in Indonesia. Public perception of people with mental disorders leads to stigma and discrimination that have negative consequences for both sufferers and their family members. The purpose of this study was to determine the relationship between mental emotional disorders and people's perceptions of mental disorders. This research is an analytic observational study with a designcross sectional.The sample in this study were employees, students and visitors of the Diponegoro National Hospital, Semarang taken by consecutive sampling method. The research instrument used a sociodemographic questionnaire, a Self Reporting Questionnaire (SRQ) 20 and a Community Attitude Towards The Mentally Ill (CAMI) questionnaire. This study found and confirmed that the subjects in this study 27.3% experienced mental emotional disorders and the majority had a counter-stigma and discrimination attitude, although there were still some who had a pro attitude towards stigma and discrimination, namely 7.3%. There is a significant correlation between emotional mental disorders and public perception of mental disorders (0.035) with a 95% confidence level. This study concludes that there is a significant relationship between emotional mental disorders and people's perceptions of mental disorders.